THE STRATEGIES TO PREVENT CASH RECEIPT FRAUD PREVENTION STRATEGY AT CV ARTA TRISNA (ELECTROPLATING AND CHEMICAL DISTRIBUTOR) - Suci Artini, Eka Dewi; Lasiyono, Untung; Sulistiyawan, Edy (International Journal of Economics, Business and Accounting Research (IJEBAR), 2025)
This study aims to analyze internal control procedures and strategies in cash receipts to prevent fraud at CV Arta Trisna Sidoarjo Branch. This study uses a qualitative descriptive method with data collection techniques through interviews, observations, and documentation. The results of the study show that the procedure for receiving cash in the company has been implemented in accordance with the theory and standards of internal control, including payments, daily reconciliation, deposits to banks, as well as supervision and separation of duties. Fraud prevention strategies are implemented through cash and giro system, CCTV monitoring, periodic audits, employee training, and separation of work functions. Comparative analysis of theory and practice shows that the elements and components of internal control in CV Arta Trisna have been effective in minimizing the risk of fraud. However, it was found that one aspect of the anti-fraud program has not been implemented, namely the consultation assistance program for employees. Overall, the company's cash internal control system is considered quite good and able to support the company's financial integrity.